Towards the future-proofing of UK infrastructure. Issue 1 (March 2016) - Masood, Tariq; McFarlane, Duncan; Parlikad, Ajith Kumar; Dora, John; Ellis, Andrew; Schooling, Jennifer
Abstract : Ensuring long-term performance from key infrastructure is essential to enable it to serve society and to maintain a sustainable economy. The future-proofing of key infrastructure involves addressing two broad issues: ( i ) resilience to unexpected or uncontrollable events (e.g., extreme weather events); ( ii ) adaptability to required changes in structure and/or operations of the infrastructure in the future. Increasingly, infrastructure owners, designers, builders, governments and operators are being required to consider possible future challenges as part of the life cycle planning for assets and systems that make up key infrastructure. A preliminary study is reported here that aimed at exploring the following questions related to infrastructure (systems): what does 'future-proofing' of infrastructural assets mean? Why and when should critical infrastructure be future-proofed? How can infrastructure assets (systems) be prepared for uncertain future events? How can future-proofing considerations be incorporated into infrastructure asset management practices? To seek answers to the above questions, two industrial workshops were conducted that brought together leading practitioners in the UK infrastructure and construction sectors, along with government policymakers. This paper captures lessons learnt from the workshops and proposes a framework for linking future-proofing into asset management considerations. Case studies of Dawlish railway and Heathrow airport are also presented.